Effectiveness of Cognitive Behavior Therapy (CBT) for Lowering Academic Anxiety in Graduate Students Completing Thesis - Nadia Farahmita; Pramesti Pradna Paramita (Psikostudia : Jurnal Psikologi, 2024)
One of the tasks of students in achieving their academic degree is completing their final assignment. Postgraduate students who are completing their thesis are expected to be able to produce scientific work, both written and oral. Students experience various difficulties that can potentially cause anxiety. Anxiety in an academic environment is called academic anxiety. This condition can reduce academic performance and achievement. One psychological assistance that can overcome this problem is Cognitive Behavior Therapy (CBT) counseling. This research aims to determine the effectiveness of Cognitive Behavior Therapy (CBT) in reducing levels of academic anxiety. This research uses a single case experimental design with research subjects namely postgraduate students who are completing their thesis. The results showed that participants experienced a decrease in academic anxiety scores, were able to evaluate negative automatic thoughts and dysfunctional assumptions and found positive things. Therefore, it can be concluded that Cognitive Behavior Therapy (CBT) effectively reduces academic anxiety in a graduate student.Salah satu tugas mahasiswa pascasarjana dalam mencapai gelar akademik yaitu menyelesaikan tugas akhir. Pada mahasiswa pascasarjana yang menyelesaikan tesis diharapkan dapat membuat karya ilmiah baik tulisan maupun lisan. Kenyataannya, mahasiswa mengalami berbagai kesulitan yang dapat berpotensi menimbulkan kecemasan. Kecemasan dalam lingkup akademik disebut kecemasan akademik. Kondisi tersebut dapat menurunkan kinerja dan pretasi akademik. Salah satu bantuan psikologis yang dapat mengatasi permasalahan tersebut yaitu dengan konseling Cognitive Behavior Therapy (CBT). Tujuan dari penelitian ini adalah untuk mengetahui efektivitas dari  Cognitive Behavior Therapy (CBT) dalam menurunkan tingkat kecemasan akademik. Penelitian ini menggunakan desain eksperimen kasus tunggal dengan subjek penelitian mahasiswa pascasarjana yang sedang menyelesaikan tesis. Hasil penelitian menunjukkan bahwa partisipan mengalami penurunan skor kecemasan akademik, mampu mengevaluasi pikiran negatif otomatis dan asumsi yang disfungsional, dan menemukan hal positif di dalam dirinya. Oleh karena itu, dapat disimpulkan bahwa Cognitive Behavior Therapy (CBT) efektif untuk menurunkan kecemasan akademik pada mahasiswa.